Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Produktivitas Karyawan PT. Maan Ghodaqo Shiddiq Lestari Jombang - Hamisah Hamisah; Mahfudiyanto Mahfudiyanto (BIMA : Journal of Business and Innovation Management, 2019)
The purpose of this study was to look for the influence of organizational culture and job satisfaction on employee productivity case studies at PT.Maan ghodaqo shiddiq sustainable. This type of research uses quantitative descriptive associative. The sampling technique used is saturated sampling. Data collection techniques using questionnaires / questionnaires, interviews, documentation and observation. In analyzing data using statistical methods, namely validity and reliability, classic assumption tests, and hypothesis testing using multiple linear regression formula. The results showed that, organizational culture partially had a significant positive effect on the productivity of PT. Maan ghodaqo shiddiq sustainable employees. Partial job satisfaction does not have an effect on the productivity of PT. Maan ghodaqo shiddiq's sustainable employees. Organizational culture and job satisfaction simultaneously affect the productivity of PT. Maan ghodaqo shiddiq's sustainable employees.